Dary z Kordoby : powiesc na tle przelomu lat 1018 i 1019 - Parnicki, Teodor (Poznan : Wydawn. Poznanskie, 1981)
A novel set in the Poland of the 11th century, in the reign of Boleslaus I.
Keywords: Poland -- History -- Boleslaus I, 992-1025 -- Fiction